Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(x^5+x+1\)
\(=\left(x^5-x^2\right)+x^2+x+1\)
\(=x^2\left(x^3-1\right)+x^2+x+1\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)\)\(+x^2+x+1\)
\(=\left[x^2\left(x-1\right)+1\right]\left(x^2+x+1\right)\)
\(=\left(x^3-x^2+1\right)\left(x^2+x+1\right)\)
b.\(x^3+x^2+4\)
=\(x^3+2x^2-x^2-2x+2x+4\)
\(=x^2\left(x+2\right)-x\left(x+2\right)+2\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2-x+2\right)\)
c.\(x^4+2x^2-24\)
\(=x^4+2x^3-2x^3-4x^2+6x^2+12x-12x-24\)
\(=x^3\left(x+2\right)-2x^2\left(x+2\right)+6x\left(x+2\right)-12\left(x+2\right)\)
\(=\left(x^3-2x^2+6x-12\right)\left(x+2\right)\)
\(=\left[x^2\left(x-2\right)+6\left(x-2\right)\right]\left(x+2\right)\)
\(=\left(x^2+6\right)\left(x-2\right)\left(x+2\right)\)
a, x^5 + x + 1 = x ^ 5 - x^2 + (x ^2 + x + 1) = x^2 ( x-1) ( x^2+x+1) + ( x^2+x+1) = ( x^2+x+1 ) ( x^3-x^2+1)
c, x^4 + 2x^2 -24 = (x^4 +6x^2) - ( 4x^2+24) = x^2( x^2+6) - 4(x^2+6) = (x^2-4)(x^2 +6 ) = (x-2)(x+2)(x^2+6)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(a^2+4b^2-5\right)^2-16\left(ab+1\right)^2\)
\(=\left(a^2+4b^2-5\right)^2-4^2\left(ab+1\right)^2\)
\(=\left(a^2+4b^2-5\right)^2-\left[4\left(ab+1\right)\right]^2\)
\(=\left(a^2+4b^2-5\right)^2-\left[4ab+4\right]^2\)
\(=\left(a^2+4b^2-5-4ab-4\right)\left(a^2+4b^2-5+4ab+4\right)\)
\(=\left(a^2+4b^2-4ab-9\right)\left(a^2+4b^2+4ab-1\right)\)
\(\left(a^2+4b^2-5\right)^2-16\left(ab+1\right)^2\)
= \(\left(a^2+4b^2-5\right)^2-\left[4\left(ab+1\right)\right]^2\)
= \(\left(a^2+4b^2-5\right)^2-\left(4ab+4\right)^2\)
= \(\left(a^2+4b^2-5-4ab-4\right)\left(a^2+4b^2-5+4ab+4\right)\)
= \(\left(a^2+4b^2-4ab-9\right)\left(a^2+4b^2+4ab-1\right)\)
= \(\left[\left(a-2b\right)^2-3^2\right]\left[\left(a+2b\right)^2-1^2\right]\)
= \(\left(a-2b-3\right)\left(a-2b+3\right)\left(a+2b-1\right)\left(a+2b+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{a^3}+\frac{1}{b^3}+\frac{1}{c^3}-\frac{3}{abc}=\left(\frac{1}{a}+\frac{1}{b}\right)^3+\left(\frac{1}{c}\right)^3-3.\frac{1}{a}.\frac{1}{b}\left(\frac{1}{a}+\frac{1}{b}\right)-\frac{3}{abc}\)
\(=\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\left[\left(\frac{1}{a}+\frac{1}{b}\right)^2-\left(\frac{1}{a}+\frac{1}{b}\right).\frac{1}{c}+\frac{1}{c^2}\right]-3.\frac{1}{a}.\frac{1}{b}\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\)
\(=\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{2}{ab}-\frac{1}{ac}-\frac{1}{bc}+\frac{1}{c^2}\right)-\frac{3}{ab}\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\)
\(=\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}-\frac{1}{ab}-\frac{1}{ac}-\frac{1}{bc}\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm:
a) \(2x^2+7x+5=\left(2x^2+2x\right)+\left(5x+5\right)=2x\left(x+1\right)+5\left(x+1\right)\)
\(=\left(2x+5\right)\left(x+1\right)\)
b) \(x^3-2x-4=\left(x^3-2x^2\right)+\left(2x^2-4x\right)+\left(2x-4\right)\)
\(=x^2\left(x-2\right)+2x\left(x-2\right)+2\left(x-2\right)=\left(x-2\right)\left(x^2+2x+2\right)\)
c) \(x^2+4x+3=\left(x^2+x\right)+\left(3x+3\right)=x\left(x+1\right)+3\left(x+1\right)\)
\(=\left(x+1\right)\left(x+3\right)\)
2x2 + 7x + 5 = 2x2 + 2x + 5x + 5 = ( 2x2 + 2x ) + ( 5x + 5 ) = 2x( x + 1 ) + 5( x + 1 ) = ( 2x + 5 )( x + 1 )
x2 + 4x + 3 = x2 + x + 3x + 3 = ( x2 + x ) + ( 3x + 3 ) = x( x + 1 ) + 3( x + 1 ) = ( x + 3 )( x + 1 )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2^{24}=(2^3)^8=8^8\)
\(3^{16}=\left(3^2\right)^8=9^8\)
vì \(8^8< 9^8\Rightarrow2^{24}< 3^{16}\)
\(2^{24}=\left(2^3\right)^8=8^8\)
\(3^{16}=\left(3^2\right)^8=9^8\)
\(8< 9\)
\(\Rightarrow8^9< 9^9\)
\(\Rightarrow2^{24}< 3^{16}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^4 + y^4=(x^2)^2+(y^2)^2
=(x^2+y^2)^2-2x^2y^2
=(x^2+y^2)^2-(√2xy)^2
=(x^2+y^2-√2 xy)(x^2+y^2+√2 xy)
\(P=a^{16}+a^8b^8+b^{16}=\left(a^8\right)^2+2a^8b^8+\left(b^8\right)^2-a^8b^8\)
\(=\left(a^8+b^8\right)^2-\left(a^4b^4\right)^2\)
\(=\left(a^8+b^8+a^4b^4\right)\left(a^8+b^8-a^4b^4\right)\)
\(=\left(a^4+b^4+a^2b^2\right)\left(a^4+b^4-a^2b^2\right)\left(a^8+b^8-a^4b^4\right)\)
\(=\left(a^2+b^2+ab\right)\left(a^2+b^2-ab\right)\left(a^8+b^8-a^4b^4\right)\left(a^4+b^4-a^2b^2\right)\)